EXPLORING INTRINSIC AND EXTRINSIC MOTIVATIONAL FACTORS INFLUENCING STUDENTS’ READING INTEREST - Sunarti; Elli Marliana (GLOBAL: Education Language and Humanity Journal, 2025)
Reading motivation plays a crucial role in students' academic success, yet the interplay between intrinsic and extrinsic factors in shaping reading interest among college students remains underexplored. This qualitative study investigates how intrinsic and extrinsic motivational factors influence the reading interest of English language education students and identifies the dominant motivational types. Data were collected through questionnaires, semi-structured interviews, and member checking involving five students and analyzed using thematic analysis. The findings revealed that intrinsic motivation, particularly curiosity, enjoyment, emotional engagement, and self-efficacy, significantly increased students' interest in reading, while extrinsic motivators such as grades, recognition, and academic obligations played a secondary, often short-term, role. The study highlights that intrinsic motivation not only fosters voluntary and sustained reading engagement but also aligns with students' autonomy and emotional connection to the text. These results confirm the principles of Self-Determination Theory and Expectancy-Value Theory, suggesting the need for pedagogical strategies that foster internal motivation. Implications for language teaching include creating environments that support autonomy and promoting meaningful, student-centered reading practices.